Gamma Radiation (60Co) Exposure and Application of Antagonists for the Suppression of Root Rot Diseases in Sunflower (Helianthus annus L.) and Mung Bean (Vigna radiata (L.) R. Wilczek) - Dawar, S.; Zaki, M.J.; Ikram, N.; Tariq, M. (Our Nature, 2011)
An experiment was carried out for the control of root rot fungi such as Fusarium spp., Macrophomina phaseolina (Tassi) Goid., and Rhizoctonia solani Kühn in Sunflower (Helianthus annus L.) and Mung bean (Vigna radiata (L.) R. Wilczek). Seeds were treated with gamma radiation (60Co) for 0, 2, 8 and 16 minutes intervals and soil was drenched with different antagonists such as Trichoderma harzianum Rifai, Pseudomonas aeruginosa (Schroeter) Migula and Rhizobium meliloti Dangeard. All the antagonists significantly increased germination percentage, shoot length, root length, shoot weight, root weight, leaf area and showed complete suppression of M. phaseolina and R. solani observed in mung bean and sunflower. In both crops, mostly growth parameters increased as the exposure of gamma rays increased whereas in some cases it decreased. P. aeruginosa and R. meliloti were observed to be satisfactory biocontrol agents followed by T. harzianum whereas all exposure time of irradiation of gamma rays (60Co) to seeds of mung bean and sunflower were found to be best. DOI: 10.3126/on.v8i1.4309